Structure and stability of metal doped tubular gold cages – comparison between potential model and density functional studies. (2016) - Priyanka,; Bansal, Sumali; Bhandari, Rajiv; Dharamvir, Keya
Abstract: We present a combined Gupta (GP) potential and Density Functional Theory (DFT) study of endohedral doping of the tubular Au24 cage with transition metal M (M=Au, Cu and Ag).The GP calculation predicts that endohedral Au doping makes the Au24 cage more stable compared to Cu and Ag atoms doping. However, DFT results predict that the Cu doped Au cage is more stable. The difference in the results of the two approaches can be explained by the observation that GP favors Au-Au bonding over Cu-Au and Ag-Au bonds. It also indicates that for its application to binary gold clusters careful reparameterization of GP is called for.